Os direitos do consumidor no plano estadual: limites federativos e os regimes estaduais de proteção ao consumidor. - Perman, Renata Gonçalves (2020)
Consumer protection through state rules is salutary, as states can regulate important aspects from regional point of view that are neglected by federal legislation, such as consumer protection code. However, the possibility for member states to protect consumer rights through local constitutions has consequences on a federal level. This states regulations, has been quite limited by the jurisprudence of the Federal Supreme Court (STF). Therefore, it is essential to examine the limitations imposed by the Supreme Court, in order to define normative criteria that fits to constitutional restrictions, therefore, must be observed by the state legislatures. In this sense, the dissertation investigates the theme of state consumer protection, unfolding it in the mentioned double aspect. First, it is proposed to discuss the possibility of defining a normative criterion to choose the set of regulatory possibilities at the state level, considering the jurisprudence of the Federal Supreme Court. Second, the discussion regarding concrete state rules - such as Law No. 16,559 of January 15, 2019 (Pernambuco State Consumer Protection Code) - is made possible, making it possible to verify compliance with the established regulatory criteria.